MANAJEMEN PENGEMBANGAN SDM DOSEN STAI IBNU RUSYD D DI ERA SOCIETY 5.0 - Supriyanti, Supriyanti; Kurniawati, Dewi; Mulyani, Dessy Kurnia; Anggraini, Soca (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to analyze the management of Human Resources (HR) development of lecturers at the Ibn Rusyd d College of Islam (STAI) in the modern era, focusing on strategies, implementation, and challenges faced. The approach used is qualitative with data collection techniques through interviews, observation, and documentation studies. The results showed that the development of human resources of lecturers at STAI Ibnu Rusyd d includes three main aspects, namely improving academic qualifications, strengthening professional competence, and fostering an Islamic work ethic. The strategies applied include the provision of further study scholarships, need-based training, and coaching through scientific forums and research activities. The implementation of this strategy is quite effective despite several obstacles, such as budget limitations, lack of active participation of some lecturers, and challenges in adapting to the latest educational technology. The research also found that the success of lecturers' human resource development management depends not only on the formal policies of the institution, but also on the commitment of the leadership, the motivation of individual lecturers, and the support of the academic ecosystem. This research is expected to be a reference for other higher education institutions in formulating adaptive and sustainable HR development policies.